Pressure‐Induced Indirect‐Direct Bandgap Transition of CsPbBr3 Single Crystal and Its Effect on Photoluminescence Quantum Yield. Issue 29 (10th August 2022) - Gong, Junbo; Zhong, Hongxia; Gao, Chan; Peng, Jiali; Liu, Xinxing; Lin, Qianqian; Fang, Guojia; Yuan, Shengjun; Zhang, Zengming; Xiao, Xudong
Abstract: Despite extensive study, the bandgap characteristics of lead halide perovskites are not well understood. Usually, these materials are considered as direct bandgap semiconductors, while their photoluminescence quantum yield (PLQY) is very low in the solid state or single crystal (SC) state. Some researchers have noted a weak indirect bandgap below the direct bandgap transition in these perovskites. Herein, application of pressure to a CsPbBr3 SC and first‐principles calculations reveal that the nature of the bandgap becomes more direct at a relatively low pressure due to decreased dynamic Rashba splitting. This effect results in a dramatic PLQY improvement, improved more than 90 times, which overturns the traditional concept that the PLQY of lead halide perovskite SC cannot exceed 10%. Application of higher pressure transformed the CsPbBr3 SC into a pure indirect bandgap phase, which can be maintained at near‐ambient pressure. It is thus proved that lead halide perovskites can induce a phase transition between direct and indirect bandgaps. In addition, distinct piezochromism is observed for a perovskite SC for the first time. This work provides a novel framework to understand the optoelectronic properties of these important materials. Abstract : High pressure exerted on CsPbBr3 single crystal lead to the photoluminescence quantum yield dramatically improved more than 90 times due to the decreased dynamic Rashba splitting. Application of higher pressure transform it into a pure indirect bandgap phase, which can be maintained at near‐ambient pressure. These phenomena provide a novel framework to understand the optoelectronic properties of perovskite materials.